Conflicting perceptions of the well-organised environment - Suhanova, Dina (Landscape Architecture and Art, 2023)
The paper presents a cross-disciplinary investigation into the intricate state of human-environment interaction. Drawing from the field of environmental psychology, it is an inquiry of the attitudes and perceptions of the human’s surrounding private and public environment, and presumably conflicting understanding, perception and individual interpretation of what well-organised and orderly environment means. It is very common to see the concept of a well-ordered environment in widespread public discourse. Depending on the context, a term encompasses various factors, such as physical, social, educational, and mental domains and can be applied not only to spatial environments but also to business and entrepreneurial, school and workplace environments, and more. Beyond creating an up-to-date understanding of the concept and understanding of orderly environment in the Latvian context, the paper aims to clarify whether there are limitations posed by conflicting understandings of the notion and set objectives, organisation of the environment, quality of life and personal and community growth. The research approach is based on the investigation through society involvement. The online questionnaire was employed to gather original and qualitative data to analyse the set topic. Additionally, the study of relevant scientific publications, bibliography and visual observations was used. The obtained results shows that conflicting opinions and perceptions exist, and they pose challenges to spatial development and quality of life. The paper contributes to the current understanding of the collectively formed environment among Latvia’s population. It can be applied to explain limitations and social colissions in spatial developments, as well as during discussions of environmental maintenance, architecture and urban quality, and overall condition of surroundings among various stakeholders.